Low-carbon high-strength cementing material and preparation method thereof

By using industrial waste slag and other modified materials, low-carbon and high-strength gelling materials are prepared, which solves the shortcomings of traditional gelling materials in terms of carbon emissions, strength and durability, and achieves high-strength and environmentally friendly building materials needs.

CN119707382AInactive Publication Date: 2025-03-28NANJING ZHONGLINGHUAHUI NEW MATERIAL SYST ENG GRP CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510134839.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-07
Publication Date
2025-03-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional gelling materials have shortcomings in carbon emissions, strength, durability and permeability, and it is difficult to meet the construction engineering needs of high strength and environmental protection requirements.

Method used

Low-carbon high-strength gelling materials are prepared through magnetic separation, grinding and stirring processes.

Benefits of technology

It significantly reduces carbon emissions, improves the strength and performance of the material, enhances the permeability, frost resistance and corrosion resistance, is suitable for high-strength construction engineering needs, and is simple in process and suitable for industrial production.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a low-carbon high-strength cementing material and a preparation method thereof. The low-carbon high-strength cementing material is prepared from the following raw materials in parts by weight: 50-80 parts of industrial waste residues, 5-15 parts of an active exciting agent, 2-8 parts of reinforced fibers, 1-5 parts of a nano modified material and 1-3 parts of an auxiliary additive. According to the low-carbon high-strength cementing material and the preparation method thereof, industrial waste residues are used as main raw materials, exploitation and consumption of natural resources are reduced, and meanwhile emission of greenhouse gases such as carbon dioxide is reduced. Compared with the traditional Portland cement, the carbon emission of the cementing material disclosed by the invention can be reduced by more than 50%. Through the reasonable formula design and the synergistic effect of the raw materials, a test piece prepared from the cementing material has excellent mechanical properties. The 28-day compressive strength can reach 60-80 MPa, the tensile strength can reach 5-8 MPa, and the requirements of various high-strength constructional engineering can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a low-carbon high-strength cementitious material and a preparation method thereof. Background Art

[0002] In the construction industry, cementitious materials are vital basic materials and are widely used in construction products such as concrete and mortar. Traditional cementitious materials are mainly silicate cement. However, the production process of silicate cement is accompanied by a large amount of energy consumption and carbon dioxide emissions. According to statistics, for every ton of silicate cement produced, about 1 ton of carbon dioxide will be emitted, which puts great pressure on the environment. With the increasing global attention to environmental protection and sustainable development, reducing carbon emissions from building materials has become an important trend in the development of the industry.

[0003] In addition, traditional cementitious materials also have certain limitations in terms of strength. In some construction projects with high strength requirements, such as high-rise buildings and long-span bridges, concrete or mortar made of traditional cementitious materials can hardly meet the growing engineering needs. In order to improve the strength, a large amount of cement or other reinforcing agents are often needed, which not only increases the cost, but also further aggravates the environmental burden.

[0004] At the same time, traditional cementitious materials also need to be improved in terms of durability and impermeability. Under harsh environmental conditions, such as marine environment, high temperature and high humidity environment, building structures made of traditional cementitious materials are prone to corrosion and cracking, which affects the service life and safety of the building. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a low-carbon high-strength cementitious material, which significantly improves the strength performance of the material while reducing carbon emissions, and has good durability and impermeability. At the same time, the present invention also provides a preparation method of the cementitious material, which solves the problems of high carbon emissions and insufficient strength of traditional cementitious materials, and provides a more environmentally friendly and superior material selection for the construction industry. The method is simple in process, easy to operate, and suitable for large-scale industrial production.

[0006] In order to achieve the above-mentioned object of the invention, the technical solution adopted by the present invention is:

[0007] A low-carbon high-strength gelling material is composed of the following raw materials by weight: 50-80 parts of industrial waste residue, 5-15 parts of active stimulant, 2-8 parts of reinforcing fiber, 1-5 parts of nano-modified material and 1-3 parts of auxiliary additive.

[0008] Furthermore, the industrial waste residue includes slag, fly ash and steel slag.

[0009] Furthermore, the active stimulant includes an alkaline stimulant and a sulfate stimulant, the alkaline stimulant includes sodium hydroxide and potassium hydroxide, and the sulfate stimulant includes sodium sulfate and calcium sulfate.

[0010] Furthermore, the reinforcing fibers include carbon fibers, glass fibers and polypropylene fibers.

[0011] Furthermore, the nano-modified material is nano-silicon dioxide.

[0012] Furthermore, the auxiliary additives include a water reducing agent, a retarder and an early strength agent.

[0013] A method for preparing a low-carbon high-strength cementitious material comprises the following steps:

[0014] Step 1: Raw material pretreatment: pre-treat industrial waste residue by magnetic separation and grinding;

[0015] Step 2: Preparation of active stimulant: dissolve the alkaline stimulant and the sulfate stimulant in water in proportion, stir evenly, and prepare an active stimulant solution for standby use;

[0016] Step 3: Mixing and stirring: Add the pre-treated industrial waste residue, reinforcing fiber, nano-modified material and auxiliary additives into the mixer to allow the raw materials to be fully mixed and reacted.

[0017] Step 4: Molding and curing: Pour the stirred cementitious material into the mold, vibrate and mold it to expel the bubbles; the molded specimens are cured under standard curing conditions.

[0018] Furthermore, in step 1, the slag is ground to a specific surface area of ​​400-500m 2 / kg, fly ash is ground to a specific surface area of ​​350-450m 2 / kg.

[0019] Furthermore, in step three, dry mixing is first performed for 3-5 minutes to achieve preliminary uniform mixing; then, the active stimulant solution is slowly added and stirring is continued for 10-15 minutes.

[0020] Furthermore, in step 4, the standard curing conditions are a temperature of 20±2° C. and a relative humidity of more than 95%.

[0021] The beneficial effects of the present invention are:

[0022] The low-carbon high-strength cementitious material and its preparation method of the present invention use industrial waste residue as the main raw material, which reduces the exploitation and consumption of natural resources and reduces the emission of greenhouse gases such as carbon dioxide. Compared with traditional silicate cement, the carbon emission of the cementitious material of the present invention can be reduced by more than 50%.

[0023] Through reasonable formula design and synergistic effect of raw materials, the test piece made of the cementitious material of the present invention has excellent mechanical properties. Its 28-day compressive strength can reach 60-80MPa, and its tensile strength can reach 5-8MPa, which can meet the needs of various high-strength construction projects.

[0024] The addition of reinforcing fibers and nano-modified materials effectively improves the microstructure of the cementitious material, and improves its impermeability, frost resistance and erosion resistance. Under harsh environmental conditions, the building structure made of the cementitious material of the present invention can maintain good performance and extend the service life of the building.

[0025] The preparation method of the invention has simple process, does not require special equipment and complicated operation flow, and is suitable for large-scale industrial production. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0027] Example 1

[0028] A low-carbon high-strength gelling material and a preparation method thereof are composed of the following raw materials in certain weight portions: 50-80 parts of industrial waste residue, 5-15 parts of active stimulant, 2-8 parts of reinforcing fiber, 1-5 parts of nano-modified material, and 1-3 parts of auxiliary additives.

[0029] Industrial waste residue: including slag, fly ash, steel slag, etc. Industrial waste residue is the main component of the cementitious material of the present invention, and its source is wide and the cost is low.

[0030] Through the reasonable combination and pretreatment of different industrial waste residues, their potential gelling activity can be fully exerted.

[0031] Slag has high potential hydraulic hardness. After pretreatment such as grinding, it can undergo hydration reaction under the action of active activators to generate products with gelling properties.

[0032] Fly ash is rich in active ingredients such as silicon and aluminum, which can work synergistically with other raw materials to improve the later strength and durability of cementitious materials.

[0033] After magnetic separation, grinding and other treatments, steel slag becomes a cementitious material with higher strength.

[0034] Activity stimulant: The function of the activity stimulant is to stimulate the potential activity of industrial waste slag and promote its hydration reaction.

[0035] Active activators include alkaline activators: sodium hydroxide, potassium hydroxide, etc. and sulfate activators: sodium sulfate, calcium sulfate, etc.

[0036] By compounding active activators, the hydration process of industrial waste residues can be optimized and the early and late strength of cementitious materials can be improved.

[0037] Reinforcement fiber: Reinforcement fiber can significantly improve the tensile strength and crack resistance of cementitious materials.

[0038] The reinforcing fibers selected in the present invention include carbon fibers, glass fibers, polypropylene fibers, and the like.

[0039] These fibers are evenly dispersed in the cementitious material to form a three-dimensional network structure, which effectively prevents the generation and expansion of cracks, thereby improving the overall mechanical properties of the material.

[0040] Nano-modified materials: Nano-modified materials can improve the microstructure of cementitious materials and increase their density and strength.

[0041] The nano-silicon dioxide selected in the present invention is used as the nano-modified material. The nano-silicon dioxide has an extremely high specific surface area and activity, can fill the pores in the cementitious material, promote the hydration reaction of the cement-based material, and enhance the interfacial bonding strength, thereby significantly improving the compressive strength and durability of the cementitious material.

[0042] Auxiliary additives: Auxiliary additives include water reducing agent, retarder, early strength agent, etc.

[0043] The function of auxiliary additives is to adjust the working performance and setting time of cementitious materials. Water reducers can reduce the water consumption of cementitious materials, improve their fluidity and construction performance; retarders can delay the setting time of cementitious materials, making it easier to mix, transport and pour during construction; and early strength agents can increase the early strength of cementitious materials and speed up construction progress.

[0044] Raw material preparation: take 60 parts of slag, 20 parts of fly ash, 5 parts of steel slag, 5 parts of sodium hydroxide, 3 parts of sodium sulfate, 3 parts of carbon fiber, 2 parts of nano-silicon dioxide, 1 part of water reducer, 0.5 parts of retarder, and 0.5 parts of early strength agent.

[0045] Raw material pretreatment: slag, fly ash and steel slag are subjected to magnetic separation and grinding respectively, so that their specific surface areas reach 450m 2 / kg、400m 2 / kg、380m 2 / kg.

[0046] Preparation of active stimulant: Dissolve sodium hydroxide and sodium sulfate in an appropriate amount of water, stir evenly, and prepare an active stimulant solution.

[0047] Mixing and stirring: Add the pretreated slag, fly ash, steel slag, carbon fiber, nano-silica, water reducer, retarder and early strength agent into the mixer, dry mix for 3 minutes, then slowly add the active activator solution and continue stirring for 12 minutes.

[0048] Molding and curing: Pour the stirred cementitious material into the mold, vibrate and shape it, and then cure it for 28 days under standard curing conditions. According to the test, the compressive strength of the specimen made of the cementitious material is 65MPa and the tensile strength is 6MPa after 28 days.

[0049] Example 2

[0050] Raw material preparation: take 50 parts of slag, 30 parts of fly ash, 10 parts of steel slag, 6 parts of potassium hydroxide, 4 parts of calcium sulfate, 4 parts of glass fiber, 3 parts of nano calcium carbonate, 1.2 parts of water reducer, 0.8 parts of retarder, and 1 part of early strength agent.

[0051] Raw material pretreatment: slag, fly ash and steel slag are subjected to magnetic separation and grinding respectively, so that their specific surface areas reach 420m 2 / kg, 430m 2 / kg, 360m 2 / kg.

[0052] Preparation of active stimulant: Dissolve potassium hydroxide and calcium sulfate in an appropriate amount of water, stir evenly, and prepare an active stimulant solution.

[0053] Mixing and stirring: Add the pretreated slag, fly ash, steel slag, glass fiber, nano calcium carbonate, water reducer, retarder and early strength agent into the mixer, dry mix for 4 minutes, then slowly add the active activator solution and continue stirring for 13 minutes.

[0054] Molding and curing: Pour the stirred cementitious material into the mold, vibrate and shape it, and then cure it for 28 days under standard curing conditions. According to the test, the compressive strength of the specimen made of the cementitious material is 70MPa and the tensile strength is 6.5MPa after 28 days.

[0055] Example 3

[0056] Raw material preparation: take 70 parts of slag, 15 parts of fly ash, 5 parts of steel slag, 4 parts of sodium hydroxide, 2 parts of sodium sulfate, 2 parts of polypropylene fiber, 1 part of nano titanium dioxide, 0.8 parts of water reducer, 0.6 parts of retarder, and 0.6 parts of early strength agent.

[0057] Raw material pretreatment: slag, fly ash and steel slag are subjected to magnetic separation and grinding respectively, so that their specific surface areas reach 480m 2 / kg、380m 2 / kg、350m 2 / kg.

[0058] Preparation of active stimulant: Dissolve sodium hydroxide and sodium sulfate in an appropriate amount of water, stir evenly, and prepare an active stimulant solution.

[0059] Mixing and stirring: Add the pretreated slag, fly ash, steel slag, polypropylene fiber, nano titanium dioxide, water reducer, retarder and early strength agent into the mixer, dry mix for 5 minutes, then slowly add the active activator solution and continue stirring for 15 minutes.

[0060] Molding and curing: Pour the stirred cementitious material into the mold, vibrate and shape it, and then cure it for 28 days under standard curing conditions. According to the test, the compressive strength of the specimen made of the cementitious material is 68MPa and the tensile strength is 5.5MPa after 28 days.

[0061] The low-carbon high-strength cementitious material and its preparation method of the present invention use industrial waste residue as the main raw material, which reduces the exploitation and consumption of natural resources and reduces the emission of greenhouse gases such as carbon dioxide. Compared with traditional silicate cement, the carbon emission of the cementitious material of the present invention can be reduced by more than 50%.

[0062] Through reasonable formula design and synergistic effect of raw materials, the test piece made of the cementitious material of the present invention has excellent mechanical properties. Its 28-day compressive strength can reach 60-80MPa, and its tensile strength can reach 5-8MPa, which can meet the needs of various high-strength construction projects.

[0063] The addition of reinforcing fibers and nano-modified materials effectively improves the microstructure of the cementitious material, and improves its impermeability, frost resistance and erosion resistance. Under harsh environmental conditions, the building structure made of the cementitious material of the present invention can maintain good performance and extend the service life of the building.

[0064] The preparation method of the invention has simple process, does not require special equipment and complicated operation flow, and is suitable for large-scale industrial production.

[0065] It can be seen from the above embodiments that the low-carbon high-strength cementitious material and the preparation method thereof of the present invention have good technical effects and practicability, and can meet the demand of the construction industry for environmentally friendly and high-strength materials.

[0066] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention shall be included in the protection scope of the present invention.

Claims

1. A low-carbon high-strength cementitious material, characterized in that: The invention is composed of the following raw materials in parts by weight: 50-80 parts of industrial waste residue, 5-15 parts of active stimulant, 2-8 parts of reinforcing fiber, 1-5 parts of nano-modified material and 1-3 parts of auxiliary additive.

2. A low-carbon high-strength cementitious material according to claim 1, characterized in that: The industrial waste residues include slag, fly ash and steel slag.

3. The low-carbon high-strength cementitious material according to claim 1, characterized in that: The active stimulant includes an alkaline stimulant and a sulfate stimulant. The alkaline stimulant includes sodium hydroxide and potassium hydroxide, and the sulfate stimulant includes sodium sulfate and calcium sulfate.

4. The low-carbon high-strength cementitious material according to claim 1, characterized in that: The reinforcing fibers include carbon fibers, glass fibers and polypropylene fibers.

5. The low-carbon high-strength cementitious material according to claim 1, characterized in that: The nano modified material is nano silicon dioxide.

6. The low-carbon high-strength cementitious material according to claim 1, characterized in that: The auxiliary additives include a water reducing agent, a retarder and an early strength agent.

7. A method for preparing a low-carbon high-strength cementitious material, comprising the low-carbon high-strength cementitious material according to any one of claims 1 to 6, characterized in that: The following steps are involved: Step 1: Raw material pretreatment: pre-treat the industrial waste residue by magnetic separation and grinding; Step 2: Preparation of active stimulant: dissolve the alkaline stimulant and the sulfate stimulant in water in proportion, stir evenly, and prepare an active stimulant solution for standby use; Step 3: Mixing and stirring: Add the pre-treated industrial waste residue, reinforcing fiber, nano-modified material and auxiliary additives into the mixer to allow the raw materials to be fully mixed and reacted. Step 4: Molding and curing: Pour the stirred cementitious material into the mold, vibrate and mold it to expel the bubbles; the molded specimens are cured under standard curing conditions.

8. The method for preparing a low-carbon high-strength cementitious material according to claim 7, characterized in that: In the step 1, the slag is ground to a specific surface area of ​​400-500m 2 / kg, fly ash is ground to a specific surface area of ​​350-450m 2 / kg.

9. The method for preparing a low-carbon high-strength cementitious material according to claim 7, characterized in that: In the step 3, dry mixing is first performed for 3-5 minutes to achieve preliminary uniform mixing; then, the active stimulant solution is slowly added and stirring is continued for 10-15 minutes.

10. The method for preparing a low-carbon high-strength cementitious material according to claim 7, characterized in that: In step 4, the standard curing conditions are a temperature of 20±2° C. and a relative humidity of 95% or more.

Citation Information

Cited By

  • Geopolymer concrete for improving construction performance based on excitant pretreatment and preparation method of geopolymer concrete

    CN121021058A

  • Geopolymer concrete with improved workability based on pre-treatment with activator and method of preparation thereof

    CN121021058B